Lepton flavor violation in the Majorana and Dirac scotogenic models - Raghavendra Srikanth Hundi (European Physical Journal C: Particles and Fields)
Abstract In this work we have considered two minimal versions of scotogenic models, where neutrinos acquire masses through a radiative mechanism. We call these two models as Majorana and Dirac scotogenic models. In the former model, neutrinos have Majorana nature, and in the later one, neutrinos are Dirac particles. These two models are related to each other in terms of additional fields and symmetries of the model. Hence, to compare these two models in future experiments, we have analyzed lepton flavor violating (LFV) processes in both of them, in the charged lepton sector. We have found that the 3-body LFV decays in both these models can get different contributions. Among all the LFV decays and after satisfying relevant constraints, we have found that $$τ → 3μ $$ τ → 3 μ can have a branching ratio as high as $$10^{-10}(10^{-11})$$ 10 - 10 ( 10 - 11 ) in the Majorana(Dirac) scotogenic model.